Typical gastroduodenal endoscopic findings in a Crohn's disease patient in remission stage - Iizuka, Masahiro (Baishideng Publishing Group Co., Limited, 2012)
A 39-year-old patient with Crohn’s disease (CD) was referred to our hospital for maintenance treatment of CD. He was diagnosed as having CD of the small and large intestines at 32 years old. He underwent partial resection of the ileum at 35 years old because of ileal perforation. He had received enteral nutritional supplement (1200 kcal/d) and metronidazole preparation (500 mg/d), and was in remission Crohn’s disease activity index 73. We performed a routine gastroduodenal endoscopic examination, which revealed the representative endoscopic findings of gastroduodenal lesions in CD, namely, bamboo-joint-like appearance of the gastric body and cardia and a notched sign in the duodenum. These findings were clearly observed by using indigo carmine dye spraying. In our patient, typical gastroduodenal findings were observed even in the remission stage, suggesting that these findings would contribute to the early diagnosis of CD not only in the active stage but also during remission.